THE EFFECTIVITY OF INTERACTIVE MULTIMEDIA AS LEARNING MEDIA TO REDUCE STUDENT™S MISCONCEPTION ON HUMAN CIRCULATORY SYSTEM (Jurnal Pelita Pendidikan, 2016)
This study was aimed to analyze the student™s misconception on human circulatory system topic andalso to determine the effectivity of interactive multimedia to reduce students misconception that experiencedby students of XII IPA grade in SMA Negeri 1 Berastagi. The study consisted of two parts. Firstly is descriptive toinvestigate student™s misconception on human circulatory system topic. Secondly quasi experimental researchused after learning process. Quasi experimental research used to determine the effectivity of interactivemultimedia in reducing student™s misconception. The experimental used one group pretest and posttest design.Instrument that used for detecting students misconception were two dimensional diagnostic test and essaytest, for reducing students misconception by using interactive multimedia as learning media. Student™smisconception reduce 42.46% in group that using interactive multimedia as learning media and reduce 14.8%in group without interactive multimedia. Based on the calculation, it was got 0.57 as gain index value in groupthat using interactive multimedia and 0.30 as gain index value in group without interactive multimedia. The ttestresult was tcount (6.598) and ttable (1.699), so tcount (6.598) > ttable (1.699). It was conclude that interactivemultimedia is effective to reduce student™s misconception on human circulatory system in SMA Negeri 1Berastagi Class XII IPA A.Y. 2016/2017.Keywords: Misconception, Students™ Misconception, Human Circulatory System